The Responsibility to Protect in the United Nations: The diffuse path to become a norm ius cogens and its imperative need - Ramos Borges, Osnarci Rafael (Revista Tribuna Internacional, 2023)
Since its formulation in 2001, the doctrine developed by the International Commission on Intervention and State Sovereignty (ICISS), endorses a universal criterion that dates back almost 100 years and, despite its initial successes, a single failure or, rather, the misrepresentation of its name for the application of a Security Council resolution, slowed down in subsequent years the progressive development of a principle which was gaining position itself in the United Nations System. The latest advances in this area are highlighted and how, in the event of being operationally applied again, it should be improved for its protection in use. At the same time, the eventual and diffuse way for it to become a norm ius cogens of the States is evaluated, but the importance of what this would represent is emphasized. Finally, we analyze why, today more than ever, the revitalization is necessary within the framework of Public International Law and the new global threats we are facing as an international community.